Response of periodontium to mineral trioxide aggregate and Biodentine: a pilot histological study on humans. (19th April 2018) - Tirone, F; Salzano, S; Piattelli, A; Perrotti, V; Iezzi, G.
Abstract: Background: The aim of this study was to investigate for the first time the histological response of human periodontium to mineral trioxide aggregate (MTA) and Biodentine. Methods: Six patients scheduled for implant full‐arch rehabilitation were randomly assigned to one of the two test groups: MTA or Biodentine treatment. For each patient, two teeth scheduled for strategic extraction were randomly assigned either to the test or to the control treatment. A lateral perforation was drilled on the root and either repaired with MTA/Biodentine or filled with gutta‐percha(control). Three months later, the teeth were extracted along with the coronal third of the alveolar bone and a portion of gingival tissue, while performing implant placement, and processed for histological analysis. Results: Biodentine resulted in less extrusion into the periodontal environment. All the materials showed good biocompatibility. A new mineralized cementum‐like tissue incorporating periodontal fibres was visible in all cases treated with MTA. A small amount of new mineralized tissue was found in two Biodentine cases but not in control cases. Biodentine resulted in less damage to the periodontal ligament. Conclusions: Bioactivity and biocompatibility of MTA were confirmed in human models. Biodentine proved to be biocompatible, but it seems not to induce cementum regeneration.